A comparative histological analysis of the femoral shaft of the crocodylomorphs Neuquensuchus universitas Fiorelli and Calvo, 2007 and Notosuchus terrestris Woodward, 1896 - García Marsa, Jordi Alexis (2018)
The record of Patagonian crocodyliforms is composed by terrestrial forms, particularly bynotosuchians. Remains of the well-known crocodile Notosuchus terrestris Woodward,1896 are very common in Upper Cretaceous outcrops of Neuquén city. Neuquensuchusuniversitas Fiorelli and Calvo, 2007 is a purported protosuchian, which was also found atthe same locality. New remains of Neuquensuchus (MACN-Pv N28; MACN-Pv N29)were published recently as coming from the same quarry of the holotype. There were alsorecovered isolated appendicular materials that can be referred to Notosuchus. In thepresent communication we studied the bone histology of twofemora, one of each taxon(Neuquensuchus, Notosuchus). At femoral mid-diaphysis, bone cortexin Neuquen suchusis made of a fibro-lamellar matrix with parallel-fibered annulus and a low amount oflongitudinal vascular canals in the cortex. In Notosuchus the growth is continuous, andthe cortex is formed by a fibro-lamellar matrix constituted by a high number oflongitudinal and reticular vascular canals. These general histologicals features differwidely between these taxa, meaning a relatively slow growth and low metabolic rate forNeuquensuchus, and contrasting with the high growth and metabolic rate showbyNotosuchus. In both cases, these crocodylomorphs differs from the Cenozoicnotosuchian Iberosuchus Antunes, 1975witha histology characters comparable with largelizardsadapted to active predation. Histologically, Neuquensuchus contrast with thecursorial Terrestrisuchus Crush, 1984, a sphenosuchia with a relatively densevascularization. Therefore, a terrestrial habitat and cursorial abilities are not necessarilyassociated with a sustained.